How to catch Santa Claus (How to catch, ,, 2023)
Children attempt to catch Santa Claus as he delivers their presents on Christmas Eve.

We could fly (Candlewick Press, 2023)
"At a sparrow's urging, a young girl feels a mysterious trembling in her arms, a lightness in her feet, a longing to be free. Her mother tells her that her Granny Liza experienced the same, as did many of their people before her. Perhaps it's time, Mama says, to slip the bonds of earth and join the journey started long ago. To hold each other tight and rise. Drawing on lyrics from the song "We Could Fly" by Rhiannon Giddens and Dirk Powell, which in turn draw on a heritage of African folklore, this incantatory dialogue between a mother and daughter paired with startlingly beautiful illustrations celebrates love, resilience, and the spiritual power of the"old-time ways"--tradition and shared cultural memory--to sustain and uplift."--

Three billy goats gruff (Orchard Books, an imprint of Scholastic, Inc, 2022)
Once there was a bridge and a terrible and VERY hungry troll lived underneath it. When the three Billy Goats Gruff decide to clip-clop across the bridge to get to the grassy ridge, the troll is already imagining all the way to prepare a delicious goat dinner. But the troll underestimates those seemingly sweet but oh-so-savvy goats!